The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1083/jcb.200405001
|View full text |Cite
|
Sign up to set email alerts
|

MT1-MMP–dependent neovessel formation within the confines of the three-dimensional extracellular matrix

Abstract: During angiogenesis, endothelial cells initiate a tissue-invasive program within an interstitial matrix comprised largely of type I collagen. Extracellular matrix–degradative enzymes, including the matrix metalloproteinases (MMPs) MMP-2 and MMP-9, are thought to play key roles in angiogenesis by binding to docking sites on the cell surface after activation by plasmin- and/or membrane-type (MT) 1-MMP–dependent processes. To identify proteinases critical to neovessel formation, an ex vivo model of angiogenesis h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
312
5
4

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 311 publications
(346 citation statements)
references
References 62 publications
22
312
5
4
Order By: Relevance
“…RT-PCR analysis of their upregulation and downregulation revealed that only gelatinase MMP-2 was constantly active, whereas MMP-9 and MMP-19 genes were active in the first days of perfused culture, but silenced at day 12, when tubular network was formed ( Figure 4B). Since MT1-MMP proteolyzes the pro-MMP-2 to its active form that can activate MMP-9, these three MMPs would form a collaborative network to drive the vasculogenic response [27]. The data presented here shows that PEGylated fibrin matrix supports the vasculogenic proteolytic program of HUVEChASC co-culture.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…RT-PCR analysis of their upregulation and downregulation revealed that only gelatinase MMP-2 was constantly active, whereas MMP-9 and MMP-19 genes were active in the first days of perfused culture, but silenced at day 12, when tubular network was formed ( Figure 4B). Since MT1-MMP proteolyzes the pro-MMP-2 to its active form that can activate MMP-9, these three MMPs would form a collaborative network to drive the vasculogenic response [27]. The data presented here shows that PEGylated fibrin matrix supports the vasculogenic proteolytic program of HUVEChASC co-culture.…”
Section: Discussionmentioning
confidence: 61%
“…Invasion and tubulogenesis only takes place if a full-length membrane-associated form of type-1 matrix metalloproteinase (MT1-MMP) is expressed [27]. Recently published analyses revealed a combinatorial MT1-MMP proteolytic program that governs endothelial cell chemotaxis, motility, and adhesion, which ultimately leads to angiogenesis [28].…”
Section: Discussionmentioning
confidence: 99%
“…Membrane type-1 matrix metalloproteinase has been implicated in the pericellular proteolysis in events ranging from normal development to malignant progression (Hotary et al, 2003;Chun et al, 2004;Holmbeck et al, 2004). MT1-MMP requires proteolytic activation and the removal of the N-terminal prodomain sequence in order to be converted into the catalytically active species (Murphy et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…MMP9 and MMP14 have another effect on the vasculature: the perivascular (or smooth muscle) cells that ensheath the endothelial cells of the blood vessels are missing or their density is significantly decreased in normal vessels and during tumour neoangiogenesis [57][58][59] . This defect is especially evident in the smaller arterioles of the brain, and many of the remaining perivascular cells have irregular morphology.…”
Section: Mmps In Blood-vessel Remodellingmentioning
confidence: 99%